Light and the Aesthetics of Perception - Volf, Carlo (The Nordic Journal of Aesthetics, 2011)
<!–StartFragment–> Light seems to be a very changeable size in our build environment. Being an immaterial building stone, light takes a very liquid shape in our design-vocabulary. It consists of an invisible material – photons – and therefore it takes no specific form in itself but is only articulated through the meeting with form. Therefore, since form has been the major theme for the aesthetics up until now, giving form to light is a complex and challenging task and reducing it to Lux and measurable numbers only an escape from facing what is actually perceived. In this way light seems to suffer from what can be called the dichotomy between the aesthetics of the objects and the aesthetics of the perception – as stated by Boehme. To improve practice this article conducts a study of our perception, focusing more on the effects of light and less on the physical light (lux). By doing so the article tries to give a better understanding of the differences of the regional lighting cultures and the influences creating the differences. The article tries to establish a link between the regional daylight and the use of artificial lighting, showing that daylight, as a background, along with our perception, are determinant factors for how the artificial lighting and the brightness of the room is perceived. The articlehereby suggests that light is not an absolute factor. This means the end of the dichotomy between daylight and artificial light – often expressed by artificial light replacing daylight – instead this article tries to establish a dialogue between the daylight and the artificial lighting. The article describes how light – this intangible building block – can become a more workable size in the aesthetic and architectural practice of today. <!–EndFragment–>